Results of Adaptation of the Methodology for Studying the Acculturation of Migrants by J. Berry on the Ukrainian Sample - Yaryna Andrushko (Insight: the psychological dimensions of society, 2023)
The article highlights the modern approach to the studyof acculturation processes on the example of Ukrainianforced migrants. The purpose of the study is to adaptthe English version of the Acculturation Questionnaireby J. Berry to Ukrainian. Methods. The translationof acculturation methods from English into Ukrainianwas carried out with the participation of two independentexperts who helped to translate and evaluatethe quality of the final version of the methodology.The study involved 502 respondents, migrants fromUkraine, who currently reside in the United Statesdue to war. The survey was conducted on the basisof RedCap. Results. Correlation analysis revealedleading indicators, with the highest correlation coefficientsbeing observed for the “integral safety indicator”and various safety subcategories (r=.807, p < .01; r=.767, p < .01; r=.787, p < .01). The internal consistencyof the questionnaire ranged from α=.793 for“sociocultural maladaptation” to α=0.934 for the “integralsafety indicator”, with a test-retest reliability coefficientof (r = .815, p < .01). Factor analysis of the dataidentified four factors, with the strongest factor containingindicators of acculturation strategies (marginalization,separation). The second factor combineddepression level, sociocultural maladaptation, life satisfaction,and anxiety level. The third factor includedcomponents related to cultural, economic, and physicalsecurity. Finally, the fourth factor consisted of a singlecomponent-self-satisfaction. Construct validity wasassessed by correlating acculturation indicators withscales from other psychodiagnostic methods, showingcausal relationships with indicators of acculturation.Discussion and conclusions. Summarizing the resultsof adapting J. Berry’s acculturation methodology, it isimportant to note that the Ukrainian-adapted versionof this methodology exhibits high psychometric characteristics,such as validity and reliability. This makesits use possible in future studies of acculturation processesamong Ukrainian migrants.